SEEDSTICK Controls Arabidopsis Fruit Size by Regulating Cytokinin Levels and FRUITFULL - Di Marzo, Maurizio; Herrera-Ubaldo, Humberto; Caporali, Elisabetta; Novák, Ondřej; Strnad, Miroslav; Balanzà, Vicente; Ezquer, Ignacio; Mendes, Marta A; de Folter, Stefan; Colombo, Lucia (Cell reports, 2020)
Upon fertilization, the ovary increases in size and undergoes a complex developmental process to become a fruit. We show that cytokinins (CKs), which are required to determine ovary size before fertilization, have to be degraded to facilitate fruit growth. The expression of CKX7, which encodes a cytosolic CK-degrading enzyme, is directly positively regulated post-fertilization by the MADS-box transcription factor STK. Similar to stk, two ckx7 mutants possess shorter fruits than wild type. Quantification of CKs reveals that stk and ckx7 mutants have high CK levels, which negatively control cell expansion during fruit development, compromising fruit growth. Overexpression of CKX7 partially complements the stk fruit phenotype, confirming a role for CK degradation in fruit development. Finally, we show that STK is required for the expression of FUL, which is essential for valve elongation. Overall, we provide insights into the link between CKs and molecular pathways that control fruit growth.
Keywords: Green Fluorescent Proteins; Arabidopsis Proteins; MADS-box; Organ Size; cell elongation; modely genetické; Flowers; květy; signální transdukce; Fruit; cytokininy; MADS Domain Proteins; Cytokinins; proteiny huseníčku; Signal Transduction; fruit size; ovoce; zelené fluorescenční proteiny; FRUITFULL; Down-Regulation; Models, Genetic; velikost orgánu; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; zeatin; cytosol; Arabidopsis; CKX7; down regulace; Cytosol; Zeatin; SEEDSTICK; proteiny domény MADS; cytokinins